Enhancing the National Competency Test: Strategic Approaches to Elevate the Quality of Health Science Graduates - Gunarmi Gunarmi (Universitas Pahlawan Tuanku Tambusai, 2025)
Students represent a crucial resource for higher education institutions, carrying immense potential to contribute to a wide range of academic fields. As the demand for highly skilled graduates intensifies, particularly within health education, the Indonesian government has introduced policies focused on improving educational quality through a comprehensive quality assurance framework. A key component of this initiative is the introduction of the National Competency Examination (UKN), designed to ensure that graduates in health fields such as nursing, midwifery, and medicine meet national competency standards and are well-prepared to compete in the global job market. This qualitative research focuses on implementing Competency Tests for nurses and midwives, with study locations covering Regional IV in Makassar and Regional II in Jakarta, providing a descriptive analysis of the findings. The results reveal that the implementation of the UKN has not yet reached the desired level of success. Challenges such as insufficient commitment from implementers and financial constraints have hindered the effective delivery of the National Competency Examination in the health education sector.